Vulcaniibacterium gelatinicum sp. nov., a moderately thermophilic bacterium isolated from a hot spring. Issue 3 (2nd January 2020) - Niu, Xue-Ke; Narsing Rao, Manik Prabhu; Dong, Zhou-Yan; Kan, Yu; Li, Qi-Rui; Huang, Jin; Zhao, Liang; Wang, Mei-Zhu; Shen, Zhi-Ping; Kang, Ying-Qian; Li, Wen-Jun
Abstract : The present study aimed to determine the taxonomic positions of strains designated R-5-52-3 T, R-5-33-5-1-2, R-5-48-2 and R-5-51-4 isolated from hot spring water samples. Cells of these strains were Gram-stain-negative, non-motile and rod-shaped. The strains shared highest 16S rRNA gene sequence similarity with Vulcaniibacterium thermophilum KCTC 32020 T (95.1%). Growth occurred at 28–55 °C, at pH 6–8 and with up to 3 % (w/v) NaCl. DNA fingerprinting, biochemical, phylogenetic and 16S rRNA gene sequence analyses suggested that R-5-52-3 T, R-5-33-5-1-2, R-5-48-2 and R-5-51-4 were different strains but belonged to the same species. Hence, R-5-52-3 T was chosen for further analysis and R-5-33-5-1-2, R-5-48-2 and R-5-51-4 were considered as additional strains of this species. R-5-52-3 T possessed Q-8 as the only quinone and iso-C15:0, iso-C11:0, C16 : 0 and iso-C17 : 0 as major fatty acids. The polar lipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, unidentified polar lipids and two unidentified phospholipids. The genomic G+C content was 71.6 mol%. Heat shock proteins (e.g. Hsp20, GroEL, DnaK and Clp ATPases) were noted in the R-5-52-3 T genome, which could suggest its protection in the hot spring environment. Pan-genome analysis showed the number of singleton gene clusters among Vulcaniibacterium members varied. Average nucleotide identity (ANI) values between R-5-52-3 T, Vulcaniibacterium tengchongense YIM 77520 T and V. thermophilum KCTC 32020 T were 80.1–85.8 %, which were below the cut-off level (95–96 %) recommended as the ANI criterion for interspecies identity. Thus, based on the above results, strain R-5-52-3 T represents a novel species of the genus Vulcaniibacterium, for which the name Vulcaniibacterium gelatinicum sp. nov. is proposed. The type strain is R-5-52-3 T (=KCTC 72061 T =CGMCC 1.16678 T ).